Educação inclusiva : o uso do método ABA no processo ensino-aprendizagem de uma criança autista em uma escola privada de educação infantil - KOURY, Tamyres Danielle Machado (2020)
This study was published in: INCLUSIVE: INCLUSIVE EDUCATION: the use of the ABA method in the teaching-learning process of an autistic child in a private school of early childhood education whose main objective was the ABA method is being used in the process of school inclusion of a child with Autistic Spectrum Disorder in early childhood education in a private school in Belém and, as a target, to self-develop a bibliographic review on Autism Spectrum Disorder; then present the concept and a description based on a bibliographic review of the ABA method; for example, to analyze how the ABA method has been used in the school record of a child with Autism Spectrum Disorder in Early Childhood Education. A bibliographic review and case study were carried out. The document was analyzed by data analysis through content analysis. The data was analyzed by the data analysis by means of the analysis of the data. The results were analyzed by this thematic version and investigated and it was organized in five sections. Thus, Autism Spectrum Disorder is a neurodevelopmental disorder that manifests itself in the period before the beginning of school life; in relation to the ABA method, is a methodological strategy that specifies the ability to adapt to the type of generalization and language adaptation program. Understand that the everyday saber can be used as a knowledge for the construction of new knowledge. And this knowledge serves as motivational tools, and facilitators for meaningful learning activity.